Pengaruh Lingkungan kerja dan Beban kerja melalui Motivasi terhadap Kinerja Karyawan pada Bank Jambi Kantor Pusat - Yerina Yerina; Arna Suryani; Sudirman Sudirman (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to determine and analyze the description of the work environment, workload, motivation, and performance of employees at Bank Jambi Head Office and analyze the influence of the work environment and workload through motivation on employee performance at Bank Jambi Head Office. This type of research uses descriptive verification research. This study uses the PLS analysis method. Based on the results of the study at Bank Jambi Head Office, it can be concluded that the work environment and workload have a positive and significant influence on employee motivation and performance. An increasingly better work environment can increase work motivation and have an impact on improving employee performance. In addition, an appropriate workload can also improve employee motivation and performance. Work motivation in this study is proven to have a positive and significant influence on employee performance, which indicates that the higher the motivation of employees, the higher the resulting performance. The results also show that motivation can be an intervening variable that mediates the influence of the work environment and workload on employee performance. Thus, improving a conducive work environment, good workload management, and increasing work motivation are important factors in improving employee performance at Bank Jambi Head Office.